Clinical relevance of nitrated beta 2-glycoprotein I in antiphospholipid syndrome: Implications for thrombosis risk. Issue 122 (August 2021) - Krilis, M.; Qi, M.; Ioannou, Y.; Zhang, J.Y.; Ahmadi, Z.; Wong, J.W.H.; Vlachoyiannopoulos, P.G.; Moutsopoulos, H.M.; Koike, T.; Sturgess, A.D.; Chong, B.H.; Krilis, S.A.; et al.
Abstract: Β2 -Glycoprotein I (β2 GPI) is an important anti-thrombotic protein and is the major auto-antigen in the antiphospholipid syndrome (APS). The clinical relevance of nitrosative stress in post translational modification of β2 GPI was examined.The effects of nitrated (n)β2 GPI on its anti-thrombotic properties and its plasma levels in primary and secondary APS were determined with appropriate clinical control groups. β2-glycoprotein I was nitrated at tyrosines 218, 275 and 309. β2 -glycoprotein I binds to lipid peroxidation modified products through Domains IV and V. Nitrated β2 GPI loses this binding (p < 0.05) and had diminished activity in inhibiting platelet adhesion to vWF under high shear flow (p < 0.01). Levels of nβ2 GPI were increased in patients with primary APS compared to patients with either secondary APS (p < 0.05), autoimmune disease without APS (p < 0.05) or non-autoimmune patients with arterial thrombosis (p < 0.01) and healthy individuals (p < 0.05).In conclusion tyrosine nitration of plasma β2 GPI is demonstrated and has important implications with regards to the pathophysiology of platelet mediated thrombosis in APS. Elevated plasma levels of nβ2 GPI in primary APS may be a risk factor for thrombosis warranting further investigation. Graphical abstract: Image 1 Highlights: The major autoantigen, B2-GPI in antiphospholipid syndrome can be nitrated. Nitration of B2-GPI inhibits binding to lipid peroxidation products. Nitrated B2-GPI loses its anti-thrombotic activity. Nitrated B2-GPI is increased in patients with primary APS compared to secondary APS and autoimmune patients without APS.